Keterampilan Berpikir Kritis dan Hubungannya dengan Keterampilan Proses Sains Siswa SMA di Manggarai - Maria Senisum (Jurnal Pendidikan dan Kebudayaan Missio, 2023)
Critical thinking skills and science process skills are two variables that can be developed in the learning process, especially science learning. These two variables can support each other, especially in science learning but can also develop separately. This study aims to determine whether there is a relationship between these two variables for high school students in the mathematics and science specialization field in the Manggarai regency. The participants involved consisted of 232 students in grade XI from five high schools. The research instrument was designed in the form of a written test for each variable. The data of both variables were analyzed using Pearson correlation formula. The results showed that the two variables are correlated with one another, where the correlation value is 0.452. This value illustrates that critical thinking and science process skills are correlated at a moderate level. In addition, the two variables show a positive correlation, which means that if the critical thinking skills variable is increased, the science process skills variable will also develop. The results of this study recommend that in the process of learning science, the activities of discovering and developing knowledge can occur by empowering critical thinking skills which are supported by the application of science process skills so that both variables can develop simultaneously